Sensitivity Analysis of a Smart 3D-Printed Hand Prosthetic. (24th February 2022) - Ige, Ebenezer Olubunmi; Adetunla, Adedotun; Awesu, Adedamola; Ajayi, Oluwaseun K.
Abstract : In this study, prosthesis performance was examined in the direction of prosthesis comfort, which may be incorporated into clinical practice as considerations for the fabrication of patient-specific prostheses. The need to produce patient-specific prosthetics is very germane to assist in orthopedic and trans-radial amputation medicine. The prosthesis makes use of a relatively simple brain-computer interface that receives electroencephalogram (EEG) signals as input and drives actuators connected to cables to actuate the 3D-printed fingers and the wrist. Both mechanical and electrical simulations were carried out to investigate the response to loading conditions, after which sensitivity analysis was conducted to validate the prosthesis performance.